469 Novel Applications of Cross-Sectional Imaging in Oncoplastic Surgical Planning for Breast Cancer Following Neoadjuvant Chemotherapy. (12th October 2021) - Begaj, A; McLean, R; Bhaskar, P
Abstract: Background: Cross-sectional imaging using MRI is most commonly used to evaluate the response to neoadjuvant chemotherapy. Furthermore, CT scan of chest, abdomen, and pelvis (CAP) is used in staging the breast cancer. This study seeks to evaluate the feasibility of using preoperative cross-sectional imaging in oncoplastic surgical planning for patients undergoing neoadjuvant chemotherapy for breast cancer. Method: All female patients who underwent neoadjuvant chemotherapy for breast cancer between January 2019 and January 2020 and underwent breast MRI pre- and post-neoadjuvant chemotherapy and staging CTCAP were included. All images were independently reviewed and analysed by two consultant breast radiologists. Chest wall symmetry, breast volume differences, skin flap thickness, arterial supply to nipple, intercostal perforators and LD pedicle were assessed on both CT and MRI. Results: Nineteen women were included in this study. Breast measurements were best made by MRI due to difficulty interpreting the CT images when supine. The majority of the patients had a dual arterial supply. There was substantial inter–observer agreement in visualisation of MICAP and AICAP. The inter–observer reliability reduced when the radiologists were asked to visualize the LICAP and the thoracodorsal artery with moderate inter–observer agreement, as the MRI images were difficult to interpret laterally. Conclusions: This study shows that MRI is suitable to detect most intercostal perforators and is the first study to highlight cross-sectional modalities for assessment of intercostal perforators and may aid preoperative surgical planning and choice of perforator. We have suggested potential addition of CT angiography in cases where the surgeon plans oncoplastic surgery.